2020
DOI: 10.3390/ijerph17113940
|View full text |Cite
|
Sign up to set email alerts
|

Twelve Weeks of Whole Body Vibration Training Improve Regucalcin, Body Composition and Physical Fitness in Postmenopausal Women: A Pilot Study

Abstract: (1) Background: Regucalcin or senescence marker protein 30 (SMP30) is a Ca2+ binding protein discovered in 1978 with multiple functions reported in the literature. However, the impact of exercise training on SMP30 in humans has not been analyzed. Aging is associated with many detrimental physiological changes that affect body composition, functional capacity, and balance. The present study aims to investigate the effects of whole body vibration (WBV) in postmenopausal women. (2) Methods: A total of 13 women (a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 46 publications
2
20
0
Order By: Relevance
“…However, in the present study, in addition to the 32.9% increase in visceral fat in OVX rats, there was also a 29.0% increase in the percentage of carcass fat (muscle) thus demonstrating a proportionality in the increase between visceral and muscle fat. This increase in body fat has been reported as being a consequence of aging in postmenopausal women, which could promote insulin resistance and an increased risk of chronic non-communicable diseases [1,2,4,5,8,11,12,16]. More importantly, the present study demonstrated that regular aerobic exercise reduced muscle fat in OVX rats to the levels of sedentary Sham rats.…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…However, in the present study, in addition to the 32.9% increase in visceral fat in OVX rats, there was also a 29.0% increase in the percentage of carcass fat (muscle) thus demonstrating a proportionality in the increase between visceral and muscle fat. This increase in body fat has been reported as being a consequence of aging in postmenopausal women, which could promote insulin resistance and an increased risk of chronic non-communicable diseases [1,2,4,5,8,11,12,16]. More importantly, the present study demonstrated that regular aerobic exercise reduced muscle fat in OVX rats to the levels of sedentary Sham rats.…”
Section: Discussionsupporting
confidence: 68%
“…Obesity is growing worldwide, being one of the main public health problems, especially in postmenopausal women [1][2][3][4]. Menopause is a natural aging process in women that promotes metabolic and body changes by increasing weight and body fat, which may increase the risk of cardiovascular diseases, obesity, diabetes, hypertension and cancer [2][3][4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, results are inconclusive, particularly regarding direct associations of distinct treatment objectives with defined types of activity, intensity, duration and frequency [19] , [20] . Unfortunately, evidence confirming direct exercise-induced bone health is scarce [21] , [22] , [23] , [24] , [25] , [26] . Inconsistent findings may result from insufficient application of exercise training principles, particularly the principles of specificity, progression and overload [27] , [28] .…”
Section: Introductionmentioning
confidence: 99%
“…CRF was delineated with the 6M WT, a validated test used in the healthy population [22][23][24]. The 6M WT is a self-paced test in which participants are asked to walk laps of a straight, 30-m corridor as quickly as possible for six minutes.…”
Section: Cardiorespiratory Testmentioning
confidence: 99%